2011
DOI: 10.1507/endocrj.k11e-012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center study on the prevalence of hypothyroidism in patients with hypercholesterolemia

Abstract: abstract. Hypercholesterolemia is one of the most representative disorders of the common diseases. To evaluate the prevalence of hypothyroidism in the population of adult hypercholesterolemia, we prospectively examined the thyroid function in patients with untreated or treated hypercholesterolemia as a multi-center survey. Subjects were the patients who were treated with some antilipemic agents or the untreated patients whose total cholesterol (TC) was over 220 mg/dL and/or LDL-cholesterol (LDL-C) over 140 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 47 publications
5
20
2
Order By: Relevance
“…Our study would confirm the correlation between NAFLD and thyroid dysfunction and a correlation between the TSH level and triglycerides (P =0.003). These observations agree with the findings of other studies that suggest a correlation between hypothyroidism and hyperlipidemia (48,49). The increase in triglycerides in patients with hypothyroidism is explained by the reduced hepatic activity of triglyceride lipase (48,50) and increased fatty acid oxidation.…”
Section: Discussionsupporting
confidence: 92%
“…Our study would confirm the correlation between NAFLD and thyroid dysfunction and a correlation between the TSH level and triglycerides (P =0.003). These observations agree with the findings of other studies that suggest a correlation between hypothyroidism and hyperlipidemia (48,49). The increase in triglycerides in patients with hypothyroidism is explained by the reduced hepatic activity of triglyceride lipase (48,50) and increased fatty acid oxidation.…”
Section: Discussionsupporting
confidence: 92%
“…Lipid levels and blood pressure differences could also be responsible for the link between thyroid and diabetic complications. A lower thyroid function may increase cholesterol and blood pressure levels, which are well established risk factors for diabetes‐related chronic complications ; however, neither total or LDL cholesterol, systolic or diastolic blood pressure differed between groups in our study, which makes this hypothesis unlikely.…”
Section: Discussioncontrasting
confidence: 60%
“…[17] In a multicentre study of prevalence of hypothyroidism in 752 hypercholesterolemic patients, primary hypothyroidism occurred in 3.7%. [15] The study by P Archana and K ashok showed a significant correlation between raised TSH levels and serum total cholesterol and LDL-cholesterol. [18] Hypothyroid patients have elevated atherogenic parameters and are at high risk for developing cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%